Determinants of consumer confidence and monetary policy dynamics in Brazil - Caetano, Rafaela Maiara; da Silva, Cleomar Gomes (Brazilian Keynesian Review, 2019)
The aim of this article is to investigate the determinants of consumer confidence in Brazil and possible impacts on monetary policy actions. The econometric methodology applied is based on Autoregressive Distributed Lag (ARDL) Models, particularly the Bounds Testing (ARDL) Approach to Cointegration. For monthly data between January 2003 and December 2016, the empirical results suggest that there is a long run relationship between consumer confidence and the other variables analyzed. As for short-run dynamics, the error correction mechanism varies between 1.9% and 8.7%, depending on the estimated model. This suggests that economic variables influence consumer confidence, and when there is a break in confidence, its recovery is very slow.